TutorMe homepage
Subjects
PRICING
COURSES
SIGN IN
Start Free Trial
Andy T.
Student at Swarthmore College
Tutor Satisfaction Guarantee
SAT II Mathematics Level 2
TutorMe
Question:

What is the distance in space between the points with coordinates (-3, 6, 7) and (2, -1 , 4)? (A) 4.36 (B) 5.92 (C) 7.91 (D) 9.11 (E) 22.25

Andy T.
Answer:

First we realize that the question is asking for a distance between points so we would have to recall the distance formula for points in 3 dimensions. The distance is the square root of the sums of the squares of the difference of each direction. Therefore in this question we would first find the differences of each direction: (-3 - 2) = -5, (6 - (-1)) = 7, (7 - 4) = 3. Then we square each difference: (-5)^2 = 25, 7^2 = 49, 3^2 = 9. Afterwards we add them all up: 25 + 49 + 9 = 83. Finally take the square root of the sum: sqrt(83) = 9.11 (D)

SAT
TutorMe
Question:

2^30 + 2^30 + 2^30 + 2^30 = A. 8^120 B. 8^30 C. 2^32 D. 2^30 E. 2^26

Andy T.
Answer:

First we should realize that if we have adding 4 of the same numbers, the addition should be the same as multiplying 4 to one of the numbers, so 2^30 + 2^30 + 2^30 + 2^30 = 4 (2^30). Then we can convert 4 to a power of 2, so 4 = 2^2. After we change the 4 into a power a two, then we can use an exponent rule which states that if you multiply numbers with the same base, then we may add the exponents instead. 4 (2^30) = 2^2(2^30) = 2^32 (C)

ACT
TutorMe
Question:

What is the product of the two real solutions of the equation: 2x = 3 - x^2 A) 3 B) 2 C) -2 D) 6 E) -3

Andy T.
Answer:

First we should start out by realizing that we need to find "two real solutions" from the given equation, so by solving for x we would find the numbers we need. 2x = 3 - x^2 => x^2 + 2x - 3 = 0 => (x + 3) * ( x - 1) = 0. Through rearranging the equation and factoring we see that (x + 3) or (x - 1) equals 0. Therefore solutions to the equation must be either x = -3 or 1. Since the question asks for the product of the solutions then the answer must be -3 * 1 = -3 (E)

Send a message explaining your
needs and Andy will reply soon.
Contact Andy
Ready now? Request a lesson.
Start Session
FAQs
What is a lesson?
A lesson is virtual lesson space on our platform where you and a tutor can communicate. You'll have the option to communicate using video/audio as well as text chat. You can also upload documents, edit papers in real time and use our cutting-edge virtual whiteboard.
How do I begin a lesson?
If the tutor is currently online, you can click the "Start Session" button above. If they are offline, you can always send them a message to schedule a lesson.
Who are TutorMe tutors?
Many of our tutors are current college students or recent graduates of top-tier universities like MIT, Harvard and USC. TutorMe has thousands of top-quality tutors available to work with you.